Information Systems for Smart Services - Beverungen, Daniel; Matzner, Martin; Janiesch, Christian (Information Systems and E-Business Management, 2017)
Digital interactions among businesses and consumers through powerful information systems and omnipresent connected devices establish today’s networked society. In this light, Service Science continues to take root as a research discipline that focuses on the integration of (digital) resources by service providers and service customers for value co-creation in service systems. Rapid advances in information technology allow for designing novel information systems that enable entirely new configurations of service systems. In turn, Service Science also leaves its mark on the design, adoption, and use of information systems and technology. With this special issue, we compile a set of timely papers that investigate selected facets of the complex interplay between information technology, information systems and Service Science to design innovative IT artifacts for smart service. This editorial opens this special issue by elaborating on our understanding of smart service.
Keywords: Information system; Smart service; Service system